Young children's physical activity levels in primary (elementary) schools: what impact does physical education lessons have for young children?. Issue 5 (3rd April 2020) - Howells, Kristy; Wellard, Ian; Woolf-May, Kate
ABSTRACT: Objectives : This paper explores the impact of physical education (PE) lessons, focusing on children aged 6–7 years, an underrepresented age in physical activity research. Methods : 10 children wore Actigraph accelerometers recording physical activity throughout the school day (9 am until 3.10 pm), for a year. Repeated measures ANOVA analysed: type of day (days including PE and days that did not) and gender ( p < .05). Results : Boys achieved 88% (girls 70%) of the recommended daily physical activity levels on PE days compared to 77% (girls 63%) on non-PE days. Significant differences occurred, boys more active than girls also PE days being more active than non-PE days. Conclusion : The novel findings indicate PE lessons significantly contributes to children's physical activity levels.